KARAKTERISTIK LEADER OF CHANGE DALAM PEMBENTUKAN BUDAYA KERJA DAN PRODUKTIVITAS KERJA BERBASIS SPRITUALITY DI KUALITA PENDIDIKAN INDONESIA (KPI) SURABAYA - Saiful Hadi; Habibi El-kafi (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2019)
This study attempts to understand the implementation of the principles of Islamic education management to make changes towards the advancement of an organization in the industrial era 4.0, that work culture and work productivity in an organization specifically in the field of educational services can be approached by growing the character of leader of change based on values spirituality. That aspects of changes in performance and work productivity can be influenced by the spiritual culture of an organization, especially in the pattern of leadership that is carried out. Also exploring leadership in this article can be seen, namely: a), how leaders create change; b) Characteristics of Leader of Changes based on spirituality; c), the Role of the Leader of Change in the formation of work culture and work productivity based on spirituality. The research method used uses a qualitative design in a descriptive way to understand deeply about leadership at KPI Surabaya, whose data is extracted through observing work dynamics and institutional performance, interviews with key informants (Executive Directors) in carrying out agency activities and efforts to document performance products KPI. Furthermore, the data obtained is processed in accordance with the theme and sub-themes obtained in the field. The research results obtained are; The way leaders create change, i.e. a) keep their employees in an uncomfortable zone, with work targets in programs that are made realistically every year so that it is measured in productivity of institutional performance, b) that the leadership character is based on the performance of the leader of the leader that partnerships. The character of leadership is more to the partnership as if there are no limits. Then personal excellence (personal excellence). Likes to explore and develop knowledge so that he at KPI is called a multy talent. as well as the most visible spiritual character of the power of honesty (integrity) and c) The Indonesian Educational Quality (KPI) Surabaya, which is forming the culture of